Raw Cow’s Milk Prevents the Development of Airway Inflammation in a Murine House Dust Mite-Induced Asthma Model - Abbring, Suzanne; Verheijden, Kim A. T.; Diks, Mara A. P.; Leusink-Muis, Athea; Hols, Gert; Baars, Ton; Garssen, Johan; van Esch, Betty C. A. M. (Frontiers in Immunology, 2017)
Epidemiological studies show an inverse relation between raw cow’s milk consumption and the development of asthma. This protective effect seems to be abolished by milk processing. Evidence for a causal relationship is however lacking and direct comparisons between raw and heat treated milk are hardly studied. This study therefore investigated the preventive capacity of raw and heated raw milk on the development of house dust mite (HDM)-induced allergic asthma in mice. Six- to seven-week-old male BALB/c mice were intranasally (i.n.) sensitized with 1 µg HDM or PBS on day 0, followed by an i.n. challenge with 10 µg HDM or PBS on days 7-11. In addition, mice were fed 0,5 mL raw cow’s milk, heated raw cow’s milk or PBS three times a week throughout the study, starting one day before sensitization. On day 14, airway hyperresponsiveness (AHR) in response to increasing doses of methacholine was measured in order to assess lung function. Bronchoalveolar lavage fluid (BALF) and lungs were furthermore collected to study the extent of airway inflammation. Raw milk prevented both HDM-induced AHR and pulmonary eosinophilic inflammation, whereas heated raw milk did not. Both milk types suppressed the Th2 polarizing chemokine CCL17 in lung homogenates and reduced lung Th2 and Th17 cell frequency. IL-4 and IL-13 production after ex vivo restimulation of lung cells with HDM was also reduced by both milk types. Local IL-5 and IL-13 concentrations were, however, only suppressed by raw milk. These findings support the asthma protective capacity of raw cow’s milk and show the importance of reduced local type 2 cytokine levels. Heated raw milk did not show an asthma protective effect, which indicates the involvement of heat sensitive components. Besides causal evidence this study provides the basis for further mechanistic studies.